Oxygen vacancy regulated selective hydrogenation of α, β-unsaturated aldehydes over LDH surface group coordinated transition metal photocatalysts. Issue 20 (7th September 2022) - Zhang, Jin; Gao, Mengting; Wang, Ruiyi; Li, Xincheng; Zhu, Pengqi; Wang, Yunwei; Zheng, Zhanfeng
Abstract : Oxygen vacancies enriched MgAl-LDH coordinated transition metal hydroxides M(OH) x photocatalysts perform excellent in the selective hydrogenation of α, β-unsaturated aldehydes to corresponding alcohols under visible light irradiation. Abstract : Selective hydrogenation of α, β-unsaturated aldehydes under mild conditions is a great challenge in the synthesis of the corresponding alcohols. Herein, we report that a series of oxygen vacancy enriched MgAl-LDH coordinated transition metal hydroxide M(OH) x (M = Ru, Pt, Pd, Ag, Rh, Fe, Co, Ni and Cu) photocatalysts were successfully prepared taking advantage of the "memory effect" of MgAl-LDH. A high yield of α, β-unsaturated alcohols was achieved under visible light irradiation. DFT simulations and DRIFTS results show that oxygen vacancies facilitate the adsorption of –CO groups and hinder the adsorption of –CC groups in cinnamaldehyde, which ensures the high selectivity to cinnamyl alcohol. The highly dispersed and electron-rich transition metal hydroxides facilitated the activation of isopropanol to provide active H species under light irradiation and then enhanced the photocatalytic performance. This study demonstrated oxygen vacancy enriched MgAl-LDH supported transition metal hydroxide M(OH) x photocatalysts for efficient selective hydrogenation under visible light irradiation.